(untitled) (Research, Society and Development, 2021)
A promising tool to act as circulating biomarkers are cellular ratios, which reflect systemic inflammation and are potential predictors for mortality prognosis in various populations. Therefore, the aim of this review is to discuss the compliance of cellular relationships and their significance in COVID-19 infection. In the present study, an integrative review was conducted. After defining the guiding question, locating and selecting articles, 491 potentially eligible publications were identified. After applying the inclusion and exclusion criteria, the sample consisted of 35 articles. It was found that elevated peripheral blood cell ratios indicate unsatisfactory clinical outcome of COVID-19. Patients with these elevated cell ratios had higher incidence of acute respiratory distress syndrome, higher rate of need for mechanical ventilation, and higher mortality rates. In conclusion, it was found that there was an association between the quantitative value of the cell ratios with the evolution of the patient with COVID-19. It was observed that the higher the neutrophil/lymphocyte, platelet/lymphocyte, and lymphocyte/monocyte ratios, the worse the prognosis of the patient infected with SARS-CoV 2. Further research is needed to confirm these findings and to compare the predictive ability of the ratios in the evolution of COVID-19 infection.